RapaNet: A Web Tool for the Co-Expression Analysis of Brassica rapa Genes. (16th June 2017) - Kim, Jiye; Jun, Kyong Mi; Kim, Joung Sug; Chae, Songhwa; Pahk, Yoon-Mok; Lee, Tae-Ho; Sohn, Soo-In; Lee, Soo In; Lim, Myung-Ho; Kim, Chang-Kug; Hur, Yoonkang; Nahm, Baek Hie; et al.
Accumulated microarray data are used for assessing gene function by providing statistical values for co-expressed genes; however, only a limited number of Web tools are available for analyzing the co-expression of genes of Brassica rapa . We have developed a Web tool called RapaNet (http://bioinfo.mju.ac.kr/arraynet/brassica300k/query/ ), which is based on a data set of 143 B rapa microarrays compiled from various organs and at different developmental stages during exposure to biotic or abiotic stress. RapaNet visualizes correlated gene expression information via correlational networks and phylogenetic trees using Pearson correlation coefficient ( r ). In addition, RapaNet provides hierarchical clustering diagrams, scatterplots of log ratio intensities, related pathway maps, and cis -element lists of promoter regions. To ascertain the functionality of RapaNet, the correlated genes encoding ribosomal protein (L7Ae), photosystem II protein D1 (psbA), and cytochrome P450 monooxygenase in glucosinolate biosynthesis (CYP79F1) were retrieved from RapaNet and compared with their Arabidopsis homologues. An analysis of the co-expressed genes revealed their shared and unique features.